Synthesis and mesomorphic properties of tetra- and octa-substituted phthalocyanines - Gürek, AG; Durmus, M; Ahsen, V (Royal Soc Chemistry, 2004)
Thia-bridged tetra- and octa-poly(oxyethylene)-substituted metal free- and Ni(II) phthalocyanines have been synthesized from the corresponding phthalonitrile derivatives in the presence of the anhydrous metal salt (NiCl2) or a strong organic base. The new compounds have been characterized by elemental analyses, UV/vis, IR, NMR and mass spectra. The mesogenic properties of these new materials were studied by differential scanning calorimetry, optical microscopy and X-ray investigations. Although octa-substituted phthalocyanine derivatives are liquid, all tetra- substituted compounds show a discotic mesophase over an extremely large temperature interval including room temperature. The relationship between the structure of the mesogenic units and the mesogenic behaviour is discussed and the influence of the different heteroatoms present in the side chains on the mesomorphic properties has been determined.
Keywords: Transition-Metal-Complexes; Nonlinear-Optical-Properties; Discotic Liquid-Crystals; Molecular Materials; Side-Chains; 2,3,9,10,16,17,23,24-Octasubstituted Phthalocyanines; Lutetium Bisphthalocyanines; Crowned-Phthalocyanines; Electronics Finalities; Electrical-Properties